Rozšíření Podnikatelského inkubátoru Brno – jih, hrubá vrchní stavba - Sankot, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Tématem této bakalářské práce je zpracování technologického řešení hrubé vrchní stavby Podnikatelského inkubátoru v Brně. Jedná se o novostavbu čtyřpodlažní, nepodsklepené budovy pro administrativní a kancelářskou činnost. Předmětem práce je zpracování technologického předpisu pro provedení prefabrikovaného železobetonového skeletu. Dalšími částmi práce, se zaměřením na etapu hrubé vrchní stavby, jsou: technická zpráva, situace se širšími vztahy dopravních tras, plán organizace výstavby s výkresem zařízení staveniště, položkový rozpočet s výkazem výměr, časový plán, kontolní a zkušební plán, návrh strojní sestavy a bezpečnost práce řešené technologické etapy.

The topic of thic bachelor thesis is processing of a technological solution of the rough top construction of the Business Incubator in Brno. It is a new four-storey, non-cellular building for administrative and office activities. The subject of this thesis is processing of a technological regulation for the prefabricated reinforced concrete skeleton. The next parts of the thesis, focused on the phase of the rough top construction, are: technical report, situation with wider relations of the transport routes, plan of the construction organization with the drawing of the building site facilities (equipment), itemized budget with the statement of acreages, schedule of work, inspection and test schedule, design of the mechanical (machine) assembly and the safety of work of the (solved) technological phase.
The Extension of the Business Incubator - South, Rough Superstructure
Keywords: Prefabrikovaný železobetonový skelet; montáž skeletu; hrubá vrchní stavba; prefabrikovaný prvek; Spiroll; technologická etapa; technologický předpis; bezpečnost práce; strojní sestava; kontrolní a zkušební plán; časový plán.; Prefabricated reinforced concrete skeleton; assembly of the skeleton; rough superstructure; prefabricated element; Spiroll; technological phase; technological regulation; safety of work; machinal assembly; inspection and test schedule; time schedule.